2020
DOI: 10.1186/s12913-020-05177-7
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation as a management tool: a national survey of hospital managers’ perceptions and use of a mandatory accreditation program in Denmark

Abstract: Background: This study aimed to examine managers' attitudes towards and use of a mandatory accreditation program in Denmark, the Danish Healthcare Quality Program (Den Danske Kvalitetsmodel [DDKM]) after it was terminated in 2015.Methods: We designed a nationwide cross-sectional online survey of all senior and middle managers in the 31 somatic and psychiatric public hospitals in Denmark. We elicited managers' attitudes towards and use of DDKM as a management using 5-point Likert scales. Regression analysis exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Of the 17 studies that addressed externally mandated audits, eight reported on the ongoing improvement process after the initial audit had taken place. Although externally initiated audits do stimulate hospitals to improve their quality of healthcare [ 39 , 44 , 51 , 68 , 83 , 93 , 104 ], there seems to be a tendency towards “complacency with past improvements” and a diminishing urgency for continued QI [ 68 , 73 , 83 , 104 , 117 ]. Similarly, it seems that the rate of improvement levels off once the external pressure diminishes [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 17 studies that addressed externally mandated audits, eight reported on the ongoing improvement process after the initial audit had taken place. Although externally initiated audits do stimulate hospitals to improve their quality of healthcare [ 39 , 44 , 51 , 68 , 83 , 93 , 104 ], there seems to be a tendency towards “complacency with past improvements” and a diminishing urgency for continued QI [ 68 , 73 , 83 , 104 , 117 ]. Similarly, it seems that the rate of improvement levels off once the external pressure diminishes [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…When a hospital started with audit activities, the process was perceived as a QI endeavour and as a challenge as the organisation attempted to align its care activities with best practices. However, after a few years, the extent of improvement reached a plateau and healthcare professionals and organisational members no longer considered the audit as a driver of change [ 83 , 93 , 104 ]. Notwithstanding these observations, the fact that organisational members had to comply with the audit requirements, had to participate in the audit process and had to collect data for the audit, fuelled the awareness and interest of healthcare professionals and organisational members in QI [ 73 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational development is also considered one of the forms of change aimed at the growth of the organization and the improvement of its performance (Khodaparasti et al 2020 ; Galy 2020 ). In general, change is the transformation from one state to another and a change in organizations or organizational change means a transformation, movement or modification from one state to another (Ellis et al 2020 ; King et al 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ellis et al ( 2020 ) this study aimed to examine Middle Managers’ attitudes in the direction of an obligatory accreditation program in Danish Healthcare Quality Program. The researchers used a nationwide cross-sectional online survey for all Middle Managers and other managers in the 31 public hospitals in Denmark.…”
Section: Literature Reviewmentioning
confidence: 99%